New Holiday Towns - Beltran Carlos; Josep Roca (European Regional Science Association (ERSA), 2011)
Since the start of tourism as rewarding and massive activity in the mid-nineteenth century, the traditional urban systems of the Spanish coast have been transformed to satisfy an increasingly changeable and demanding typology of tourist. Among the different models of urban development that have taken place so far, this study examines the phenomenon of New Holiday Towns: New Towns planned for mass tourism, with an own identity and certain degree of economic and/or political autonomy. These ex-novo settlements are built over tabula rasa and based on a large scale, master plan with an independent urban structure, thanks to strong business investment and the support and commitment from local government. The keys to success: leisure as a consumer product and an efficient marketing. The objective of this paper is to reflect on this model of tourist development that is spreading internationally. For this, firstly the economic, social and political reality that facilitates its emergence and subsequent development was studied. A few cases of New Holiday Towns were studied chronologically, noting the notable difference between the first appeared and the current ones. And finally, a sociological study was carried out in a specific case: Marina d'Or, in the municipality of Oropesa del Mar, Castellón. I wanted to know the intensity of use that neighbors make of public space, ways of inhabiting urban space in daily life, what kind of user frequent these towns, why, for how long, what are their customs, satisfaction level, valuation of urban space… To do this I used a quantitative methodology, the survey, and ethnography as a qualitative method of analysis through participant observation. This study questions this model of tourist development, arguing that its urban management and exclusive reliance on the tourist activity turn New Holiday Towns into Non-places. Is being a Non-place a symptom for the future stagnation of these New Towns? In that Case, what would be the panacea for them?
Keywords: 330